Analisa ketidakberaturan horizontal dan vertikal pada struktur gedung beton bertulang - Nurul Hidayati; Hariyadi; Mukhta Riqi Sab’it Tibaq (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2023)
The behavior of regular and irregular building structures in resisting earthquake loads will certainly be different, so structural modeling must be done in such a way as to form a safe structure. The building in this study is L-shaped with an area of 2079.52 m2 with 6 floors and 28 m of total height. Earthquake load modeling in this study uses the equivalent static analysis method and design spectrum response about SNI concrete 2847-2019 and SNI earthquake 1726-2019. This study aims to investigate the behavior of multilevel reinforced concrete structures that experience horizontal and vertical irregularities due to earthquake loads as seen from the displacement and drift ratios that occurs is based on the results of numerical analysis. Based on the results of research on the geometry of the structure with vertical irregularities, it shows that the structure does not have Type 1a, Type 1b, Type 2, Type 3, Type 4, Type 5a and Type 5b irregularities. Thus the structure can be planned without considering the requirements to satisfy vertical irregularities. The geometry of the structure with horizontal irregularities shows that the structure has no irregularities in Type 1a, Type 1b, Type 3, Type 4 and Type 5. Meanwhile in Type 2 the structure is stated to have irregular inside angles, so the design force of the diaphragm on the structure must be increased by 25% at the planning stage.